Clinical features and diagnostic imaging of cholangiolocellular carcinoma compared with other primary liver cancers: a surgical perspective. (16th October 2020) - Takamura, Hiroyuki; Gabata, Ryousuke; Obatake, Yoshinao; Nakanuma, Shinichi; Hayashi, Hironori; Kozaka, Kazuto; Sasaki, Motoko; Okazaki, Mitsuyoshi; Yamaguchi, Takahisa; Shimbashi, Hiroyuki; Terai, Shiro; Okamoto, Koichi; et al.
Background and Objectives: Although cholangiolocellular carcinoma is considered a combined hepatocellular and cholangiocarcinoma, we feel that this classification is not appropriate. Therefore, we compared the diagnostic imaging findings, surgical prognosis, and pathological features of cholangiolocellular carcinoma with those of other combined hepatocellular and cholangiocarcinoma subtypes, hepatocellular carcinoma, and cholangiocarcinoma. Methods: The study patients included 7 with classical type combined hepatocellular and cholangiocarcinoma; 8 with stem cell feature, intermediate type combined hepatocellular and cholangiocarcinoma; 13 with cholangiolocellular carcinoma; 58 with cholangiocarcinoma; and 359 with hepatocellular carcinoma. All patients underwent hepatectomy or living-related donor liver transplantation from 2001 to 2014. Results: cholangiolocellular carcinoma could be distinguished from hepatocellular carcinom, other combined hepatocellular and cholangiocarcinoma subtypes, and cholangiocarcinoma by the presence of intratumoral Glisson's pedicle, hepatic vein penetration, and tumor-staining pattern on angiography-assisted CT. Cholangiolocellular carcinoma was associated with a significantly lower SUV-max than that of cholangiocarcinoma on FDG-PET. Hepatocellular carcinoma, classical type, and cholangiolocellular carcinoma had significantly better prognoses than stem cell feature, intermediate type and cholangiocarcinoma. A cholangiocarcinoma component was detected in cholangiolocellular carcinoma that progressed to the hepatic hilum, and the cholangiocarcinoma component was found in perineural invasion and lymph node metastases. Conclusions: From the viewpoint of surgeon, cholangiolocellular carcinoma should be classified as a good-prognosis subtype of biliary tract carcinoma because of its tendency to differentiate into cholangiocarcinoma during its progression, and its distinctive imaging and few recurrence rates different from other combined hepatocellular and cholangiocarcinoma subtypes.